Simultaneous and sequential price competition in heterogeneous duopoly markets: Experimental evidence - Dorothea Kübler; Wieland Müller (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
We investigate simultaneous and sequential price competition in duopoly markets with differentiated products. In both markets symmetric firms are repeatedly and randomly matched. The strategy method is used to elicit behavior in the sequential market. We find that average leader prices in the sequential market are higher than average prices in the simultaneous market, just as predicted by the theory, whereas average follower prices are not above average prices in the simultaneous market, in contrast to the theoretical prediction. Furthermore, second movers gain from the sequential structure in comparison to simultaneous-move markets whereas first movers do not. As in theory, there is a significant first-mover disadvantage when firms decide sequentially. Finally, to assess the robustness of our findings, we report the results of control treatments varying the matching scheme and the mode of eliciting choices (strategy method vs. standard sequential play).
urn:nbn:de:kobv:11-10051147
Keywords: C92; D43; 330; experimental economics; heterogeneous duopoly; price leadership; simultaneous play; first-mover disadvantage; strategy method